A clinical study of complications of diphtheria - Arya, Pooja; Maharia, Manphool S.; Kadela, Ramesh K.; ., Deepchand (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Diphtheria is an acute infectious preventable disease of childhood caused by C. diphtheriae. Diphtheria is a localized infection of mucous membrane or skin. Methods: The present study was carried out in the Department of Otorhinolaryngology S.P. Medical College and associated group of hospital. In this study all cases of diphtheria and all age groups which attended ENT OPD and emergency department during period from 1/1/2010 to 31/12/2010 were included. Results: In the present study highest numbers of cases were recorded among 5-10 years of age followed by 0-5 year of age group. 57.59% patients were male and 42.41% patients were female. It was found that occurrence of diphtheria was highest in month November and October and was quit frequent during September and December. No cases during April, June and July. It was observed that most common post diphtheria complication was myocarditis (23.42%) followed by neurological complication. Conclusions: In order to prevent complication of the disease active immunization is customary and in order to detect the disease at early stage and for prompt treatment masses should be educated regarding the dreadful nature of the disease.